2013
DOI: 10.1109/tia.2013.2265935
|View full text |Cite
|
Sign up to set email alerts
|

A Thermal Management Approach to Fault-Resilient Design of Three-Level IGCT-Based NPC Converters

Abstract: The three-level (3L) neutral-point-clamped (NPC) converter, introduced by Nabae in 1981, has become the most popular converter topology for high-power medium-voltage industrial drives. Responsible for driving key processes in various industries, high availability of these converters is mandatory, since their maintenance or replacement implies downtimes incompatible with the requirements of the production processes. In this context, this paper discusses a thermal management approach to a fault-resilient design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Another thermal management technique focusing on the fault-resilient design of an integrated gate-commutated thyristor (IGCT) based 3-level NPC converter is discussed in [255]. The results obtained showed that through the optimized design of busbars and regulation of temperature, the IGCTs could withstand converter shoot-through situations even if there is a failure in the circuit breakers.…”
Section: B Thermal Management During Fault Conditionmentioning
confidence: 99%
“…Another thermal management technique focusing on the fault-resilient design of an integrated gate-commutated thyristor (IGCT) based 3-level NPC converter is discussed in [255]. The results obtained showed that through the optimized design of busbars and regulation of temperature, the IGCTs could withstand converter shoot-through situations even if there is a failure in the circuit breakers.…”
Section: B Thermal Management During Fault Conditionmentioning
confidence: 99%
“…Responsible for driving key processes in modern systems, the high availability of the ANPC and NPC power converters is mandatory, since their maintenance or replacement imply downtimes incompatible with the requirements of the production processes [7]- [9]. The faulttolerant operation of such converters has been addressed in the technical literature, but the main pro result in more complexity and higher parts c…”
mentioning
confidence: 99%